Evidence for a black hole in a radio-quiet quasar nucleus - Blundell, K; Beasley, A; Lacy, M; Garrington, S (Institute of Physics Publishing, 1996)
We present the first milli-arcsecond resolution radio images of a radio-quiet quasar, detecting a high brightness temperature core with data from the VLBA. On maps made with lower-frequency data from MERLIN and the VLA jets appear to emanate from the core in opposite directions, which correspond to radio-emission on arcsecond scales seen with the VLA at higher frequencies. These provide strong evidence for a black-hole--based jet-producing central engine, rather than a starburst, being responsible for the compact radio emission in this radio-quiet quasar.